A Survey of Traditional Chinese Drinking Games - Wan, Yao; Dechsubha, Thawascha (Technium Social Sciences Journal, 2022)
China has a long history of wine-brewing. Traditional Chinese drinking games are a unique and mysterious part of the Chinese drinking culture. In this paper, we deal with the development of Chinese wine first, and then we take big events as reference to uncover the history of the traditional Chinese drinking games chronologically. After introducing the representative drinking games from each dynasty, it could help people understand the general development of the traditional Chinese drinking games. The results show: (1) the Chinese wine-brewing origins from the saccharomycetes, matures in Tang and Song Dynasties, and popularizes in Yuan, Ming, and Qing Dynasties. (2) The first traditional Chinese drinking game is pitch-pot, and it emerges in the later of Spring and Autumn Period. Its system grows mature in the Tang Dynasty. The Qing Dynasty is a united period for the collection of traditional Chinese drinking games.